Impact of salt intake on inflammation markers in cardiovascular disease: a retrospective observational case-control study - Dmitrii O. Dragunov; Anna V. Sokolova; Vadim M. Mitrokhin; Grigorii P. Arutyunov (Кубанский научный медицинский вестник, 2021)
Background. Salt intake currently poses a serious threat due to the cardiovascular challenge incurred by excessive sodium consumption.Objectives. The identification of markers associated with high salt intake in hypertensive patients.Methods. A retrospective observational case-control study surveyed 251 persons, including 194 hypertensive patients with stable salt intake. The intake was assessed in the “Charlton: SaltScreener” questionnaire. General, biochemical blood panels and interleukin levels (IL-1, IL-2, IL-4, IL-6, IL-8, IL-10, IL-18) were evaluated in the outcome of medical examination. Statistical data processing was performed with R using the RStudio software.Results. The mean patient age in survey was 72.47 ± 9.8 years, women prevailed in the selected cohort (n = 151, 60.1%). All patients were assigned in cohorts by the daily salt intake rate, ≤5 g (n = 12), 6–10 g (n = 144), >10 g salt per day (n = 38). The largest cohort (74.2%) united patients consuming 6–10 g salt per day, whereas only 6.2% patients consumed salt <5 g/day. Final analysis included patients consuming ≥6 g/day and having a C-reactive protein (CRP) level <20 mg/L. The analysis elicited an association between the monocyte count, CRP and salt intake towards the statement that higher salt intake leads to higher monocyte counts at CRP <20 mg/L in blood. Modelling revealed a close monocyte count–salt intake relationship, with a low-to-high intake transition sharply increasing the probability of elevated absolute monocyte count in blood provided the CRP level is <20 mg/L.Conclusion. The study infers a direct relationship between salt intake >10 g/day and blood monocyte count. However, its significance ceases at CRP rising to ≥20 mg/L.